B-Mode Ultrasonography and Acoustic Radiation Force Impulse Elastography in Evaluation of Urothelial Carcinoma in Dogs - Ana Paula Luiz De Oliveira; Bruna Bressianini Lima; Denise Jaques Ramos; Gabriela Castro Lopes Evangelista; Igor Cezar Kniphoff Da Cruz; Ricardo Andrés Ramirez Uscategui; Andrigo Barboza de Nardi; Marcus Antônio Rossi Feliciano (Animals)
Bladder tumors in dogs represent approximately 2% of all malignant lesions recorded, with urothelial carcinoma being the most common and aggressive form. This study aimed to characterize the elastographic properties of canine urothelial carcinoma using ARFI (Acoustic Radiation Force Impulse) elastography and to evaluate its diagnostic capacity. Seven dogs with urothelial carcinoma and nine healthy dogs were evaluated, comparing shear wave velocity (SWV) and bladder wall thickness between the groups. The results showed that SWV was significantly higher in dogs with urothelial carcinoma (median of 2.53 m/s) compared with healthy dogs (median of 1.41 m/s) (p = 0.0045). Bladder wall thickness was also greater in dogs with carcinoma (0.28 ± 0.05 cm) compared to healthy dogs (0.14 ± 0.26 cm) (p = 0.0003). Receiver operating characteristic (ROC) curve analysis revealed a high sensitivity (100%) and specificity (88.9%) for SWV in differentiating healthy and neoplastic tissues. These findings suggest that ARFI elastography is a promising tool for diagnosing urothelial carcinoma in dogs, offering a noninvasive and quantitative approach that can complement traditional diagnostic methods. ARFI elastography may aid in early diagnosis and clinical management, improving the prognosis of patients with bladder neoplasia.